FACTORS ASSOCIATED WITH SMOKING AMONG USERS OF THE FAMILY HEALTH STRATEGY - Erildo Vicente Müller; Makcine Timm da Silva; Clóris Regina Blanski Grden; Péricles Martim Reche; Pollyanna Kássia de Oliveira Borges; Jacy Aurélia Vieira de Sousa (Universidade Federal do Paraná, 2017)
The aim was to identify factors associated with smoking among users of the Family Health Strategy. A cross-sectional, descriptive and analytic epidemiological study. The sample by convenience encompassed 100 individuals who were users of a Family Health Unit from a city in the center-south region of the Brazilian State of Paraná. There was a predominance of women (n=63; 63%), with a mean age of 49.5 years, Caucasian (n=82; 82%), who had completed junior high school (n=21; 21%) and who were married (n=49; 49%). Mean daily cigarette consumption was 17.7 cigarettes/day and 56 (56%) participants had a very high or high degree of dependence on nicotine. An association was observed between mean smoking duration and age (p=0.001), marital status - widowed (p=0.035), high cholesterol (p=0.035), use of antihypertensives (p=0.031) and very high degree of dependence on nicotine (p=0.008). The identification of the factors associated with smoking makes it possible for the health team to seek and plan prevention strategies, treatment and monitoring of smokers.